Modernization Without Change: Decision-Making Process in the Mercosur Parliament - Medeiros,Marcelo de Almeida (2016)
This article analyzes the role of Mercosur's Parliament within Mercosur’s institutional design and decision-making process by associating its institutional arrangements to potential outcomes over representativeness. Generally, it discusses how representative Mercosur’s chosen mechanism for ruling seats in its Parliament, the so-called “citizen representation”, is and how that might affect coordination trends and solutions concerning political conflicts. Hence, the article investigates such mechanism in terms of its consequences for representativeness. The method relies on a Game Theoretical perspective through the application of the Banzhaf Index, which seeks to precisely measure the power of each player as their capacity to influence decisions. The article shows that, although the criteria used by the “citizen representation” is more representative than the previously used mechanism (in which all of Mercosur’s member-states had the same number of seats) in terms of the actual population within Mercosur, not all the changes brought by the mechanism are an advance when it comes to democratic participation. Brazil will be the most powerful in influencing the final decision once the mechanism is fully implemented; Argentina, in turn, will have the same amount of power in influencing the final outcome than will have Venezuela even though its population is 30% larger than the latter.